Bentuk Penyajian Talempong Unggan Pada Acara Khitanan Di Kecamatan Sumpur Kudus Kabupaten Sijunjung - Yulianti Rahayu Nengsih; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2019)
This article aims to describe the performance form of Talempong Unggan at the circumcision event in Sumpur Kudus District, Sijunjung Regency. This type of research was qualitative which used descriptive method. The main instrument in this study was the researcher and assisted with supporting instruments such as stationery and cameras. Data collection techniques were carried out by doing observation, literature study and interviews. Steps of data analysis were taken to collect data, analyze data, describe data and make conclusions. The result shows that the performance of Talempong Unggan in the circumcision event contains two forms, namely the first in the form of procession on the road and the second in the form of sitting with cross-legged in front of the house / on the porch of the house. In the procession of Talempong Pacik in circumcision event, Unggan functions as accompaniment music from Bako family to accompnay children to be circumcised. The performance of Talempong Unggan which is played in front of the house in circumcision functions as entertainment music and waits for children who will be circumcised.